Playing Blocks Against Early Childhood Social-Emotional Development - Cinna, Paramidhita Buana; Wahira, Wahira; Asrifan, Andi; Herlina, Herlina (PT. Riset Press International, 2026)
Play has many roles in a child's development. It's the same with playing blocks. Blocks are toys that we often see in school, blocks are educational games that are made of wood or foam and are played by shaping the desired building. This study aims to determine the influence of block games on children's social-emotional development and to determine the level of early childhood social-emotional development before and after being given block play activities. The research method used the One Group Pretest–Posttest design. In this design, there is only one group of subjects who are given treatment in the form of block play. through pretest and posttest which is carried out using direct observation of the research sample. The data analysis used was descriptive analysis and inferential analysis. The results of the study show that block play activities have a significant and positive influence on improving the social-emotional development of children aged 5-6 years. Descriptively, there was a substantial increase in social-emotional development scores. This is shown by a significant increase in the average score, from 75.38 in the pretest stage to 92.92 in the posttest stage. The results of hypothesis testing using the Wilcoxon Signed Rank Test confirmed the existence of a significant influence. A p-value of 0.001498 was obtained, which is far below the significance level. These findings support the rejection of the Null Hypothesis (), which means that there is a significant difference between pretest and posttest scores.